Cognitive Semantic Analysis of Metaphors in the Lyrics of Sorai by Nadin Amizah - Harahap, Annisah Inriani; Armis, Muhammad Khairi (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2025)
The research aims to analyze the use of metaphor in the lyrics of the song